A Semantics Analysis of Personification in Percy Bysshe Shelley’s Poetry - Aulika, Andien Nurfadlilah; Gunawan, Hero (Universitas Galuh, 2024)
This research aims to identify the types of personification and the contextual meaning behind the personification used in Percy Bysshe Shelley’s poetry. This research uses descriptive qualitative method as the purpose of making this research is to analyze the types of personification and the contextual meaning behind the personification used. This research uses semantics studies with several theoretical sources that refer to the theory of Personification from Paxson (1994) and the theory of contextual meaning by Chaer (2009). The results of the research, 41 data contain personification expression was found. There are 12 data of Prosopographia and 29 Prosopopopeia. 12 data of Prosopographia is classified into five sub-classes: Emotions, Characteristic, Concept, State and Time. The research reveals 7 data of Prosopographia in Concept category, 2 data in State category, 3 data in Time category, and 0 data found in Emotions and Characteristic categories. Out of 29 data of Prosopopopeia, the researcher also classified the data into three sub-classes: Living things, Places and Inanimate object. There are 3 data of Prosopopopeia in Living things category, 3 data in Places category and 23 data in Inanimate objects category.